The hydrolysis of phosphatidylinositol monolayers at an air/water interface by the calcium-ion-dependent phosphatidylinositol phosphodiesterase of pig brain. - Hirasawa, K (1981)
1. The activity of Ca2+-dependent phosphatidylinositol phosphodiesterase (EC 3.1.4.10) of pig brain against [32P]phosphatidylinositol monolayers at an air/water interface has been measured. As the monolayer pressure was increased a sharp cut-off of enzymic hydrolysis occurred at 33 X 10(-3) N/m. 2. The addition of either phosphatidic acid, phosphatidylglycerol or oleyl alcohol increased the film pressure at which cut off occurred, as well as increasing the rate of hydrolysis at lower pressures. 3. The rate of hydrolysis, but not the cut-off pressure, was markedly increased by oleic acid and slightly increased by phosphatidylethanolamine. 4. Phosphatidylcholine, palmitoylcholine and octadecylamine decreased the cut-off pressure, as well as the enzymic activity below this pressure. 5. Stearic acid and stearyl alcohol had no effect on either the cut-off pressure or the activity. 6. All activators decreased the length of the lag phase before enzyme activity began, and phosphatidylcholine increased it. 7. These results are compared with the stimulatory and inhibitory effects of various amphiphiles observed previously with phosphatidylinositol dispersions [Irvine, Hemington & Dawson (1979) Eur. J. Biochem. 99, 525-530], and their possible relevance to the control of the phosphatidylinositol phosphodiesterase in vivo are discussed.